AZJ 2010
DOI: 10.33910/1999-4079-2010-2-4-363-364
|View full text |Cite
|
Sign up to set email alerts
|

New Data on Some Water Birds From the Khabarovskii Krai Province

Abstract: Резюме. Представлены новые сведения о распространении, численности, характере пребывания 11 редких или недостаточно изученных видов птиц. Summary. New data on the abundance, distribution and residency status of 11 rare and insufficiently studied bird species in Khabarovskii Krai are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, two individuals were seen 18 May 2011 in the mixed colony of Gray Heron and Great Cormorant Phalacrocorax carbo (Linnaeus, 1758) in the vicinity of Khabarovsk (Pronkevich et al 2011). At the left bank of the Amur River, 7 km up the Emoron River, 5 May 2017, a group of six individuals was recorded; 27 April 2018, four birds were observed at the same place (Pronkevich 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, two individuals were seen 18 May 2011 in the mixed colony of Gray Heron and Great Cormorant Phalacrocorax carbo (Linnaeus, 1758) in the vicinity of Khabarovsk (Pronkevich et al 2011). At the left bank of the Amur River, 7 km up the Emoron River, 5 May 2017, a group of six individuals was recorded; 27 April 2018, four birds were observed at the same place (Pronkevich 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009–2013, a series of avian surveys conducted throughout the greater Academy, Schaste, and Tugur Bay regions in central Khabarovsk Krai revealed that Schaste Bay (mainland Russia, ~20 km west of Sakhalin Island) may be an important breeding area for greenshanks as numerous pairs were found displaying brood-rearing behaviours (Pronkevich and Oleinikov 2010, Pronkevich et al 2011a, b, Pronkevich 2013, Pronkevich and Voronov 2013). During 2019–2021, we concentrated nest-searching efforts here and found a total of nine (six active and three inactive) greenshank nests.…”
Section: Introductionmentioning
confidence: 99%